Variably saturated groundwater modelling for optimizing managed aquifer recharge using trench infiltration. Issue 13 (18th January 2015) - Heilweil, Victor M.; Benoit, Jerome; Healy, Richard W.
Abstract Spreading‐basin methods have resulted in more than 130 million cubic metres of recharge to the unconfined Navajo Sandstone of southern Utah in the past decade, but infiltration rates have slowed in recent years because of reduced hydraulic gradients and (or) clogging. Trench infiltration is a promising alternative technique for increasing recharge and minimizing evaporation. This paper uses a variably saturated flow model to further investigate the relative importance of the following variables on rates of trench infiltration to unconfined aquifers: saturated hydraulic conductivity, trench spacing and dimensions, initial water‐table depth, alternate wet/dry periods, and number of parallel trenches. Modelling results showed (1) increased infiltration with higher hydraulic conductivity, deeper initial water tables, and larger spacing between parallel trenches, (2) deeper or wider trenches do not substantially increase infiltration, (3) alternating wet/dry periods result in less overall infiltration than keeping the trenches continuously full, and (4) larger numbers of parallel trenches within a fixed area increases infiltration but with a diminishing effect as trench spacing becomes tighter. An empirical equation for estimating expected trench infiltration rates as a function of hydraulic conductivity and initial water‐table depth was derived and can be used for evaluating feasibility of trench infiltration in other hydrogeologic settings. Copyright © 2014 John Wiley & Sons, Ltd.